Efficacy of continuous preperitoneal ropivacaine infusion in women with cesarean section: A prospective, randomized controlled, single blinded study - Woo Jeng Kim; Eui-Jin Cho; Gyul Jung; In Seon Hwang; Jong Bun Kim; Yoonho Kim; Hee Joung Lee; Yeon-Hee Kim (Heliyon)
Background: Adequate postoperative pain management after cesarean section is important for the prognosis of both mother and infant. However, excessive prescription of opioid analgesics has become a concern. This study evaluated the efficacy of local continuous subfascial infusion of ropivacaine in relieving postoperative pain and reducing opioid requirements in postpartum women with cesarean section. Methods: Seventy eligible women undergoing cesarean section were randomly allocated to the ropivacaine and the normal saline group for continuous subfascial wound infiltration. All patients received additional fentanyl through an intravenous patient-controlled analgesia pump. Pain score using the visual analog scale, opioid consumption through pump, and requirements for other analgesics were postoperatively measured within 8 h, 1 day, and 2 days after surgery. Statistical analysis was performed with independent t-tests for continuous variables and Chi-square tests for categorical variables. Paired Wilcoxon and student's t-tests were used for paired samples. Results: Sixty-nine patients (35 in the study and 34 in the control group) were analyzed. The mean VAS scores were lower in the study group all three periods, with significance achieved at day 2 (2.74 ± 0.95 versus 3.41 ± 1.33, p = 0.028). The intravenous fentanyl consumptions were significantly lower in the study group at all three periods. Total administration of additional non-opioid analgesics including ketorolac, propacetamol, and pethidine was higher in the control group. Conclusions: Continuous subfascial ropivacaine infusion is effective in relieving pain and reducing opioid-based analgesia and other analgesics requirements.